A novel diagnostic model for tuberculous meningitis using Bayesian latent class analysis - Dong, THK; Donovan, J; Ngoc, NM; Thu, DDA; Nghia, HDT; Oanh, PKN; Phu, NH; Hang, VTT; Vinh Chau, NV; Thuong Thuong, NT; Tan, LV; Thwaites, GE; et al. (BioMed Central, 2024)
Background Diagnosis of tuberculous meningitis (TBM) is hampered by the lack of a gold standard. Current microbiological tests lack sensitivity and clinical diagnostic approaches are subjective. We therefore built a diagnostic model that can be used before microbiological test results are known.